Oncogene status as a diagnostic tool in ocular and cutaneous melanoma. (April 2016) - Griewank, Klaus G.; Schilling, Bastian; Scholz, Simone L.; Metz, Claudia H.; Livingstone, Elisabeth; Sucker, Antje; Möller, Inga; Reis, Henning; Franklin, Cindy; Cosgarea, Ioana; Hillen, Uwe; Steuhl, Klaus-Peter; et al.
Abstract: The majority of human tumours can be easily and correctly diagnosed based on clinical information and pathological assessment. In some cases however, correct diagnosis can prove difficult. In such cases, molecular approaches can be of significant diagnostic value. In recent years, the understanding of genetic alterations has greatly increased. In cutaneous melanoma, it is now well recognised, that 70–80% of tumours harbour BRAF and NRAS mutations. These mutations never occur in uveal melanoma. On the other hand activating GNAQ and GNA11 mutations are found in ∼90% of uveal melanomas, and are exceptionally rare in other melanomas (<1%). Here, we demonstrate a number of melanoma cases, where distinguishing if a tumour was of cutaneous or ocular origin was not possible based on clinical and pathological assessment. In these cases there was either atypical clinical presentation or metastasis of unclear primary. Histological distinction between uveal and cutaneous melanomas, especially at the stage of metastasis, is not reliable as they can be morphologically very similar. In all cases we present, a simple genetic assessment of oncogene mutation status was able to clearly define the melanoma type. This type of genetic assessment is of great diagnostic value and due to its simplicity could be performed in routine clinical practice even in smaller institutions. Highlights: Correctly classifying tumours is crucial for selecting correct treatment and follow-up protocols. Determining the origin of melanocytic tumours can on occasion be challenging. Oncogene status can frequently help correctly determine tumour subtype and origin. Determining oncogene status should be considered not only of potential therapeutic but also diagnostic value.